Living in the Light : The Bangladesh Solar Home Systems Story - Cabraal, Anil (World Bank, Washington, DC, 2021)
The Bangladesh Solar Home Systems (SHS) Program is the largest national program in the world for off-grid electrification. Begun in 2003, SHS installations under the Program ended in 2018. It is the longest, continuously operating off-grid electrification program in the world. The SHS Program was led and implemented by the Infrastructure Development Company Ltd (IDCOL). Over a 15-year period beginning in 2003, over 4.1 million SHS were sold and supported using a competitive business model that offered consumers a choice of quality SHS, made affordable with financing. About 14 percent of the Bangladesh population (2011 Census), about 20 million people, obtained electricity services through the SHS Program. The SHS Program enabled one-quarter of the unelectrified rural population in 2003 to obtain electricity services far sooner than would have been possible with grid electricity. SHS were mainly used in rural homes for lighting, mobile phone charging, and powering TVs and radios. They were also used in about 200,000 rural businesses and religious facilities. The program led to SHS becoming a credible electricity source in Bangladesh and, more broadly, to the acceptance of solar photovoltaics (PV) as an electricity generation technology. Building on the credibility gained, SHS distribution to the poorest households under other government programs and commercial SHS sales picked up in later years along with IDCOL-financed sales. While the Bangladesh SHS Program will continue to 2021, this report covers the program from 2003 to 2018, describes its benefits and costs, and discusses how the program adapted to inevitable changes and risks over the 15-year period. It draws lessons that can help guide the development and implementation of other sustainable off-grid electrification programs.